Visual sensitivity to irregularities in periodic tiling patterns - J. Farley Norman; Yulia Mishchuk; Maria Carmichael; Ash Sheehan; Evan Hagan (Scientific Reports)
Abstract A single experiment was conducted to evaluate the sensitivity of human vision to irregularities in regular (repetitive) patterns that tile the plane; mathematicians have been investigating such patterns (tilings) for hundreds of years. The stimulus patterns in the current study were composed of obliquely oriented line segments and strongly resemble patterns used in traditional art. In the experiment, the pattern density was manipulated as well as the magnitude of pattern alteration. Signal detection methodology was used, such that the observers’ task was to indicate for each presented pattern whether it was perfectly regular or it had been altered such that the periodicity was broken. The obtained results indicate that human observers are moderately sensitive (overall d’ value was 1.76) at detecting violations of the periodicity of regular patterns that tile the plane. High performance (d’ values greater than 2.0) only occurs, however, when pattern elements repeat over small spatial scales.